Pharmacokinetics, pharmacodynamics, safety and tolerability of cilofexor, a novel nonsteroidal Farnesoid X receptor agonist, in healthy volunteers. Issue 3 (15th January 2023) - Younis, Islam R.; Kirby, Brian J.; Billin, Andrew N.; Xiao, Deqing; Song, Qinghua; Watkins, Timothy R.; Othman, Ahmed A.
Abstract: Cilofexor is a nonsteroidal farnesoid X receptor (FXR) agonist being evaluated for treatment of nonalcoholic steatohepatitis (NASH) and primary sclerosing cholangitis (PSC). This work characterized the pharmacokinetics, pharmacodynamic, safety, and tolerability of cilofexor in healthy participants. Cilofexor single and multiple once‐daily doses (10 to 300 mg fasting or fed and twice‐daily doses [15 and 50 mg; fed]; tablet formulation) were evaluated. In each cohort, participants were randomized to active drug or placebo in a 4:1 ratio (planned n  = 15/cohort). Multiple dosing was for 14 days. Pharmacokinetic and pharmacodynamic samples were collected and safety and tolerability were assessed. Overall, 120 participants were enrolled in the study and 118 participants received at least one dose of study drug. Cilofexor pharmacokinetics followed bi‐exponential disposition and its exposure increased in a less‐than‐dose‐proportional manner over the 10 to 300 mg dose range, with no significant accumulation with repeated dosing. Moderate‐fat meal reduced cilofexor area under the plasma concentration versus time curve (AUC) by 21% to 45%. Cilofexor increased plasma levels of fibroblast growth factor19 (FGF19) and reduced the serum bile acid intermediate 7α‐hydroxy‐4‐cholesten‐3‐one (C4) and bile acids in an exposure‐dependent manner. Cilofexor doses >30 mg appeared to achieve the plateau of intestinal FXR activation. Cilofexor was generally well tolerated; all treatment‐emergent adverse events (TEAEs) were mild or moderate in severity, with headache being the most frequently observed TEAE. The pharmacokinetics pharmacodynamic safety, and tolerability results from this study supported further evaluations, and informed dose selection, of cilofexor in phase II studies in patients with NASH and PSC.